6=9x-8x+3

Simple and best practice solution for 6=9x-8x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6=9x-8x+3 equation:


Simplifying
6 = 9x + -8x + 3

Reorder the terms:
6 = 3 + 9x + -8x

Combine like terms: 9x + -8x = 1x
6 = 3 + 1x

Solving
6 = 3 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
6 + -1x = 3 + 1x + -1x

Combine like terms: 1x + -1x = 0
6 + -1x = 3 + 0
6 + -1x = 3

Add '-6' to each side of the equation.
6 + -6 + -1x = 3 + -6

Combine like terms: 6 + -6 = 0
0 + -1x = 3 + -6
-1x = 3 + -6

Combine like terms: 3 + -6 = -3
-1x = -3

Divide each side by '-1'.
x = 3

Simplifying
x = 3

See similar equations:

| -9x-6y+3= | | 18p-3+7p+31= | | (13+a)+13= | | 0.80x+0.55(80)=0.40(100) | | y-12y= | | 12=m+2 | | 5(6x+35)+7(x+1)=u | | -2y+10=-2(2y+3) | | x-4=-13 | | 16x^2+y^2-16y=0 | | r+10=15 | | 16x^2+y^2=16y | | -2+x=26 | | 2.1=x-6.1 | | (12)(6)6=x | | 3p=18 | | -10x=70 | | -7x=-168 | | -10.1x=30.3 | | 100(84)=96x | | -10x-20=-190 | | 4x+10x=56 | | 12z=-8 | | -11=x+4 | | 3x^2y+6x^2y^2-144xy^3= | | x^2-3x=-8 | | x=4+-3y | | x^2-18+77= | | 4(2x+-1)=27+3(2x-5) | | x(x+3)=18 | | 38=25+2y | | 7p=6p^2-3 |

Equations solver categories